Distorções no processo decisório do Supremo Tribunal Federal: delegação para relatores e assessores - Nascimento, Cristiano de Jesus Pereira (2017)
The brazilian Supreme Court has taken an unprecedented leading role in brazilian institutional history. Following the great relevance of Court's decisions, it is crucial to reflect on the quality of deliberation and decision-making process. Nowadays, there are three key factors involving decision-making process: the overwhelming caseload, the rapporteur empowering and the increasing number of law clerks. The burning caseload has lead to the rapporteur empowering and the law clerk explosion. Both measures were effective to cope with the caseload, but compromised the judicial decision-making process by the lack of collegiality and shallow judgment. The outstanding delegation of judicial functions and the bureaucratization of judicial decision-making process jeopardize the Court's mission and compromise the stability, integrity and consistency of its decisions